ANALISIS PENGENDALIAN KUALITAS PRODUK DALAM UPAYA MENGURANGI JUMLAH KERUSAKAN PRODUK DENGAN MENGGUNAKAN METODE SIX SIGMA DAN KAIZEN (Studi Kasus Pabrik Roti Bakar Azhari) - Naufal Fakhri Gustyanto; Ayudyah Eka Apsari (CV. ALIM'SPUBLISHING, 2024)
Azhari Bakar Bread Factory is an MSME domiciled in Rejowinangun, Kotagede, Yogyakarta. In the production process, this factory can produce 7807 pieces of bread in a month, of the total production that month 57 pieces of bread are defective. To reduce defects, quality control is needed. Quality control aims to produce products in the form of goods or services that comply with the desired and planned standards, as well as improve the quality of products that do not comply with predetermined standards and possibly maintain appropriate quality. This research uses the Six Sigma and Kaizen methods by showing factual data and comparing it with existing theories to find things that need to be added, improved, or maintained. This research found that the sigma process capability calculated for 1 month was 2.97 with a possible damage of 3661.21 for one million production. From these results, it can be said that the company has not implemented quality control completely properly and correctly because it is still far from the target level of 6 sigma, therefore the company needs to carry out quality control on defective products. The factor that causes production defects is the human factor. machines, methods, materials, and environment.